Global justice, rights and risk - Martins, António Manuel (Estudios de Filosofía, 2008)
Pluralism and multiculturalism are today accepted as characteristic of modern societies. As a simple affirmation of plurality and incompatibility of doxastic systems - activities and ways of life to which some value is recognized - pluralism is no more than commonplace. It acquires another status and philosophical relevance, from the moment in which it indicates the conviction or the thesis that the pluralism of ethical, philosophical or religious doctrines is a permanent and undeniable trace of modern democratic societies, and not a simple historical contingency, eventually surmountable through recourse to any process of reduction to a value that serves as a common denominator for the plurality in question. [Fragment]